CARICOM Secretariat PMP training course - cohort 1 (CCS GeorgetownGY, 2011)
Presents the projects of the CARICOM Secretariat staff who were part of the PMP training course conducted through the auspices of the Secretariat. Includes project charter, project plans and interim and final reports.
Contents: Executive summary. - Attachment I : CARICOM Exercise Park detailed project documents. - Attachment 2 : Support to the Library of the Graham's Halll Primary School detailed project document. - Attachment 2.A: Support for the Graham's Hall Primary School Library : project closure report. - Computerisation of the CARICOM Secretariat's pension scheme CompuPenV1.0 presented by Team GAMMA.